Tracking biomass burning markers in atmospheric aerosols: Robust quantification of anhydrosugars and reference material evaluation - Rosa Pérez-Pastor; Susana García-Alonso; María Leco; Óscar Pindado (Environmental Science and Pollution Research, 2026)
Biomass burning significantly impacts air quality and regional climate processes, making the precise quantification of its molecular tracers critical for source apportionment models. To ensure regional data comparability, establishing robust and standardized analytical frameworks is essential. This study presents a validated method for determining key biomass burning tracers: levoglucosan, galactosan, and mannosan. Accelerated solvent extraction (ASE) with a dichloromethane:methanol mixture was selected as the extraction procedure, due to its high precision, automation and minimized sample handling, followed by BSTFA derivatization and GC/MS. The method showed high linearity ( R 2 > 0.9987), repeatability below 6%, and limits of detection lower than 0.02 mg L⁻ 1 . Accuracy was evaluated using SRM 2787 (Fine particulate matter), yielding relative errors between 1% and 7.4%. In contrast, significant variability was observed for levoglucosan concentrations in SRM 1649b (Urban dust), depending on extraction conditions, highlighting the strong influence of matrix aging and methodological factors on older reference materials. Chromatographic calibration was identified as the dominant contribution to the calculated uncertainty budget. The resulting expanded uncertainties fully comply with upcoming European air quality monitoring directives.